2006
DOI: 10.2471/blt.05.021865
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests in HIV management: a review of clinical and laboratory strategies to monitor HIV-infected individuals in developing countries

Abstract: We conducted a systematic review on the performance of diagnostic tests for clinical and laboratory monitoring of HIVinfected adults in developing countries. Diagnostic test information collected from computerized databases, bibliographies and the Internet were categorized as clinical (non-laboratory patient information), immunologic (information from immunologic laboratory tests), or virologic (information from virologic laboratory tests). Of the 51 studies selected for the review 28 assessed immunologic test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Overuse of costly determinations is undesirable. However, timely introduction of antiretroviral therapy is essential in preventing AIDS and death, and underuse of monitoring in developing countries has detrimental consequences [9] , [10] . Two recent simulation studies concluded that improved HIV detection and pre-treatment CD4 monitoring in resource-poor settings could save several life-years per person taking antiretroviral treatment and could be cost-effective by preventing opportunistic infections [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Overuse of costly determinations is undesirable. However, timely introduction of antiretroviral therapy is essential in preventing AIDS and death, and underuse of monitoring in developing countries has detrimental consequences [9] , [10] . Two recent simulation studies concluded that improved HIV detection and pre-treatment CD4 monitoring in resource-poor settings could save several life-years per person taking antiretroviral treatment and could be cost-effective by preventing opportunistic infections [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…While these technologies are the standard of care in well-resourced countries, the benefits of these tools must be weighed against their costs in resource-limited countries [1-4]. Some argue that complicated monitoring technologies impede the overall goal – to deliver antiretroviral therapy to as many patients as possible.…”
Section: Introductionmentioning
confidence: 99%
“…172 Comprehensive studies including test methods, statistical methods, test results and estimates and participant data are crucial information for program management and policy making for appropriate disease monitoring and management. 173 By using a specific RNA aptamer, a piezoelectric biosensor for the protein trans-activator of transcription (Tat) of HIV-1 was built, through binding between the biotinylated aptamer and gold surface-deposited streptavidin. 56 This model system exhibited comparable performance to that of the homologous anti-Tat immunosensor.…”
Section: Hiv/aidsmentioning
confidence: 99%